Qualitative and quantitative voluntary carbon disclosure diversely affects Chinese firm performance - Taizhe Xu; Daiju Narita (Discover Sustainability)
Abstract In the context of escalating global efforts to address climate change, firms are increasingly engaging in voluntary carbon disclosure (VCD). While the financial impacts of VCD have gained increasing research attention, the marginal effects of qualitative and quantitative VCD remain underexplored. Therefore, this study aims to investigate the distinct effects of qualitative versus quantitative VCD on both accounting-based and market-based measures of financial performance (FP). We estimate a two-way fixed effects (TWFE) model utilizing a panel dataset of over 3000 Chinese listed firms for the period 2014–2021. The data are obtained from the China Stock Market and Accounting Database (CSMAR). To analyze the marginal effects, dummy variables of general VCD and quantitative VCD are constructed representing the qualitative and quantitative VCD. We first estimate the overall effect of VCD on FP, revealing a negative impact on accounting-based FP but a positive one on market-based FP. We further explore the marginal effects of qualitative and quantitative VCD, which is also the primary contribution of this study. We find that the negative effect on accounting-based FP stems primarily from the marginal effects of qualitative VCD. Conversely, the positive influence on market-based FP is mainly driven by the marginal effect of quantitative VCD. Our analysis indicates that quantitative VCD enhances firms’ market performance without significantly impacting short-term profitability, while qualitative VCD offers no benefit and may even harm short-term profitability. Based on our findings, we advise against disclosing carbon information solely in a qualitative manner. Instead, firm managers are encouraged to prioritize engagement in competitive and high-quality quantitative VCD, given its economic payoff. For policymakers, it is advisable to formulate best practice guidelines for VCD. Such guidelines would reduce disclosure costs while simultaneously enhancing information quality.